Pemberdayaan Mahasiswa Melalui Peningkatan Kompetensi Jurnalistik Untuk Meningkatkan Publikasi - Misbah Fikrianto; Sabar Lesman (AMMA : Jurnal Pengabdian Masyarakat, 2024)
Increasing student competency is a process to provide complete knowledge, attitudes and skills. Based on the condition of students at the Faculty of Teacher Training and Education, As-Syafi'iyah Islamic University, around 95% require increased competency in the field of Journalism. The number of students in the Guidance and Counseling study program is 183 students, the number of students in the English Language Education study program is 111 students, and the number of students in the Master of Educational Technology study program is 237 students. The problem faced is: How to empower students through increasing journalistic competency? How do we provide increased competency which includes: The basics of journalism, the process of writing for the media, Journalism Professional Ethics, and others. Empowering students in the field of journalism can add contributors to news writing, activity coverage, and others. Publications in the process of education, learning, training and student activities are very important. This creates strategic potential for turning students into young journalists. The student empowerment program was continued by collaborating with the Indonesian Muslim Journalist Brotherhood (PJMI) for follow-up activities. The results of student empowerment will provide benefits to the Faculty of Teacher Training and Education, Asysyafi'iyah Islamic University.